A systems pharmacology model for gene therapy in sickle cell disease. (17th June 2021) - Zheng, Bo; Wille, Lucia; Peppel, Karsten; Hagen, David; Matteson, Andrew; Ahlers, Jeffrey; Schaff, James; Hua, Fei; Yuraszeck, Theresa; Cobbina, Enoch; Apgar, Joshua F.; Burke, John M.; et al.
Abstract: We developed a mathematical model for autologous stem cell therapy to cure sickle cell disease (SCD). Experimental therapies using this approach seek to engraft stem cells containing a curative gene. These stem cells are expected to produce a lifelong supply of red blood cells (RBCs) containing an anti‐sickling hemoglobin. This complex, multistep treatment is expensive, and there is limited patient data available from early clinical trials. Our objective was to quantify the impact of treatment parameters, such as initial stem cell dose, efficiency of lentiviral transduction, and degree of bone marrow preconditioning on engraftment efficiency, peripheral RBC numbers, and anti‐sickling hemoglobin levels over time. We used ordinary differential equations to model RBC production from progenitor cells in the bone marrow, and hemoglobin assembly from its constituent globin monomers. The model recapitulates observed RBC and hemoglobin levels in healthy and SCD phenotypes. Treatment simulations predict dynamics of stem cell engraftment and RBC containing the therapeutic gene product. Post‐treatment dynamics show an early phase of reconstitution due to short lived stem cells, followed by a sustained RBC production from stable engraftment of long‐term stem cells. This biphasic behavior was previously reported in the literature. Sensitivity analysis of the model quantified relationships between treatment parameters and efficacy. The initial dose of transduced stem cells, and the intensity of myeloablative bone marrow preconditioning are predicted to most positively impact long‐term outcomes. The quantitative systems pharmacology approach used here demonstrates the value of model‐assisted therapeutic design for gene therapies in SCD.